Study on Physiological Effects of Nicotine - Saima Sharif; Shagufta Naz (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
Nicotine is thought to be the main component present in the smoke of tobacco, which works as a neurotoxic and largely accounts for most of the deleterious effects on body functions. Nicotine affects metabolic and biological processes, hormone secretions as well as hematopoietic systems. It was observed that when the mice were given doses of nicotine it alters their hematological parameters, lipid profile, liver enzymes and reproductive hormones.